An ambiguity in Habermas’s argument against liberal eugenics - Schäfer, Leon-Philip (Bioethics, 2019)
In his book The future of human nature, Jürgen Habermas argues against a scenario of liberal eugenics, in which parents are free to prenatally manipulate their children’s genetic constitution via germline interventions. In this paper, I draw attention to the fact that his species-ethical line of argument is pervaded by a substantial ambiguity between an argument from actual intervention (AAI) and an argument from mere controllability (AMC). Whereas the first argument focuses on threats for the autonomy and equality of prenatally modified persons, the second argument takes all human beings, whether they have been modified or not, into account. Hence, when invoking Habermas in these debates, bioethicists need to consider carefully which argument they are referring to.